On 2-absorbing primary and weakly 2-Absorbing elements in multiplicative lattices - (:unkn) unknown (Forum-Editrice Universitaria Udinese SRL, 2015)
In this paper, we introduce the concept of 2-absorbing primary and weakly 2-absorbing primary elements which are generalizations of primary and weakly primary elements in multiplicative lattices. Let L be a multiplicative lattice. A proper element q of L is said to be a (weakly) 2-absorbing primary element of L if whenever a,b,c ∈ L with (0 ≠ abc ≤ q) abc ≤ q implies either ab ≤ q or ac ≤ √q or bc ≤ √q. Some properties of 2-absorbing primary and weakly 2-absorbing primary elements are presented and relations among prime, primary, 2-absorbing, weakly 2-absorbing, 2-absorbing primary and weakly 2-absorbing primary elements are investigated. Furthermore, we determine 2-absorbing primary elements in some special lattices and give a new characterization for principal element domains in terms of 2-absorbing primary elements.
Keywords: 2-absorbing element; 2-absorbing primary element; Multiplicative lattice; Primary element; Prime element